Tongue-Strengthening Exercises in Healthy Older Adults: Does Exercise Load Matter? A Randomized Controlled Trial - Van den Steen, Leen; Vanderwegen, Jan; Guns, Cindy; Elen, Rik; De Bodt, Marc; Van Nuffelen, Gwen (Dysphagia, 2019)
Tongue-strengthening exercises (TSE) are based on the principles of exercise and motor learning, including intensity. Intensity is manipulated by gradually adjusting the resistive load. This randomized controlled trial (RCT) investigates the effect of three different values resistive load during TSE in healthy older adults. Sixty subjects completed 8 weeks of TSE while exercising with Iowa Oral Performance Instrument (IOPI). They were randomly distributed to 4 different treatment arms: 3 exercise groups (EG1: n = 15; EG2: n = 16, EG3: n = 16) and 1 control group performing lip-strengthening exercises (CG: n = 13). Values of resistive load for EG1, EG2, and EG3 were 100, 80, and 60% 1RM, respectively. Anterior and posterior maximal isometric pressures (MIP A , MIP P ) were measured at baseline, after 4 and 8 weeks of training and 4 weeks post-training. MIP A and MIP P in the EG were significantly higher than in the CG at all time points, except baseline. No significant differences between EG were found, but some trends were observable. Anteriorly, the higher the resistive load, the higher the increase in MIP. Posteriorly, 100% 1RM caused the highest values, followed by 60% and 80% 1RM. No detraining effects were measured. The degree of exercise load had a significant negative effect on the registered success rate. This RCT confirms the efficacy of TSE in healthy older adults. For MIP A and MIP P , TSE at a resistive load of 100% 1RM are the most efficient choice in this population, while lowering the resistive load will lead to an increased success rate. No detraining effects were registered.